Pendistribusian Dana Zakat pada Program Beasiswa Satu Keluarga Satu Sarjana di Badan Amil Zakat Nasional Jawa Timur - Irsalina Almashuri; Bambang Subandi (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2021)
This research aim to answer question. The question is regarding the implementation of zakat distribution to one-family-one-bachelor scholarship program at National Amil Zakat of East Java. The researcher used qualitative approach, spesifically case study type. This research used interview, observation, and documentation as data collection techniques. The finding of this research indicates that the distribution process at National Amil Zakat Institution of East Java is through transferring the zakat to Mustahik of one-family-one-bachelor scholarship program. BAZNAS that based in regency in East Java is a distribution channel to reach Mustahik outside Surabaya and Sidoarjo. Baznas that based in regency also distributes zakat to the mustahik through transfer as well. At this point, the distribution process in Baznas of East Java is directly distributed to mustahik.